The Effect of Liquidity on Performance of Consumer Cyclical Companies Listed on the Indonesian Stock Exchange - Yasminawati, Anjani; Safitri, Dilla Ulfiani; Lestari, Henny Setyo (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study examines the effect of liquidity on company performance in the cyclical consumer sector listed on the Indonesian Stock Exchange (IDX) with a focus on 40 companies for a five years from 2019-2023. This study uses panel data regression analysis and purposive sampling techniques, with the dependent variable being profitability as measured by return on equity (ROE). Independent variables consist of current ratio and quick ratio, while control variables include tangible assets, company size, company age, inflation rate, and GDP growth. The results show that the current ratio produces a positive effect on company performance, while the quick ratio shows a negative effect. In addition, tangible assets and company size do not have a significant effect on company performance. The age of the company proved to have a negative influence, while the inflation rate did not show a significant influence. On the other hand, GDP has a positive influence on company performance. The results of this study can be taken into consideration for companies in making strategic decisions to increase profitability in the cyclical consumer sector.